Pengaruh Pembelajaran Technopreneur, Marketing dan Lingkungan Sosial terhadap Entrepreneurial intention melalui Inkubasi Bisnis - Nur Laila Indra Sapitra Wahyu Ilyasari; Tuwoso Tuwoso; Wahyu Sakti Gunawan Irianto (Ideguru: Jurnal Karya Ilmiah Guru, 2026)
This study aims to analyze the influence of technopreneur, marketing, and social linkage learning on entrepreneurial intention through business incubation in vocational school students in Lamongan Regency. This study uses a quantitative approach with an explanatory research design. In this study, a sample of 180 students consisting of classes XI and XII of fashion design skills was used in four vocational schools in Lamongan Regency. In this study, Partial LeastSquare Structural Equation Modeling (PLS-SEM) data analysis was used. The results of this study show that social business incubation has a positive and significant effect on entrepreneurial intention. The social and marketing environment also has a positive and significant effect on business incubation. However, technopreneur and marketing learning do not have a significant effect directly on entrepreneurial intention. Indirect effects testing showed that business incubation was able to mediate the influence of the social environment and marketing on entrepreneurial intention, but it was unable to mediate the influence of technopreneur learning. These findings confirm that real entrepreneurial experience through business incubation programs has a strategic role in shaping the entrepreneurial intentions of vocational school students. Therefore, strengthening entrepreneurship learning needs to be directed to an experience-based approach that is integrated with business incubation in order to be able to increase students' entrepreneurial readiness in a sustainable manner.